Alteraciones morfológicas en placentas de madres expuestas a pesticidas - Villanueva I., María Elena; Sanhueza L., Verónica; Reyes G., Janice; Neira C., Leslie (Revista Hospital Clínico Universidad de Chile, 2010)
Several studies had stablished a correlation between prenatal exposure to pesticides and congenital malformations in the newborn. The interest of the investigators has been centered in the possibles mechanisms of these malformations. Mots of the investigations studies the enzimatical ways that are affected by the substances that mothers were exposed during the pregnancy. In relation to morphology, the few published studies have been done by groups of Mexicans and brazilians investigators. The main findings are about vascular alterations and placental maturity.